Handloom and Handicrafts: An Attitudinal Survey among the Youths of Arunachal Pradesh - Sharjo, Pema Dorjee; Garg, Arindam (The Eastasouth Management and Business, 2025)
The handloom and handicrafts sector is one of the country's largest and oldest cottage industries. This sector is the largest job provider in the country after agriculture. It directly or indirectly provides more than 6 million employees across the country. This sector plays an im-portant role in creating job opportunities for women, scheduled Tribes, scheduled castes, and other OBCs, thus promoting balanced regional development of the country. This sector is also important for promoting exports. India is one of the largest exporters of handlooms and handicrafts internationally. A country like India has a large pro-portion of youth. This helps the government produce more working people and contribute more to the economic development of the country; they have an important role to play in the promotion and preservation of handloom and handicraft practices. They are bridges that connect the older generation to the coming generation. Youths learn from the older generation and pass such knowledge to the com-ing generation. Thus it is important to study the different perspectives of our youths for the long-term development of the country.